"Arabesques": The Making and Breaking of a Concept in Renaissance Italy. Issue 1 (2nd January 2023) - Brennan, Robert
Abstract: "Arabesques" ( arabeschi ) took shape as a term and concept in sixteenth-century Italy to describe motifs deriving from Islamic art. The formation of the concept reflects a complex interplay between art making and art theory, which played out differently across different media. In metalwork, the arabesque was conceptualized in tandem with conscious projects of imperialist appropriation, whereas in needlework it furnished a theoretical basis for a highly conflicted affirmation of female artists. In the long term, these countervailing developments laid the groundwork for increasingly racialized identifications between the arabesque and the grotesque.